Inkarnasi Fisika Kuantum Yesus dalam Pola Relasi Generasi Milenial dan Gereja dalam Masa Pandemi Covid-19 - Bima, Yustiwati Angu (Marturia, 2020)
Abstract Several generations often times will simultaneously become members of a church that leads to an issue called gap generation, which is a common challenge faced by the church. Apparently, the church will not only face a changing time but also, they should deal with a various and wide mindset of this sandwich generation. This phenomenon will be discussed in this paper that focuses on millennials. Some suggestions are firstly the church needs to concede the millennials who are also a part of their community supported by some theory of generations from Strauss and Howe. Secondly, after the acknowledgment, the church needs to build relationships that aligns well with their characters. Thus, the quantum physics concept suggested by Keith Anderson will be mapped out to reframe the incarnation of Jesus Christ as an example of a relationship pattern that the church can make use and develop it for their millennials, especially during the Covid-19 pandemic. Abstrak Beberapa generasi secara bersamaan dapat menjadi anggota gereja yang kemudian membuat ‘gap generation’ menjadi sebuah tantangan yang umum dihadapi oleh gereja. Gereja tidak hanya menghadapi perubahan zaman tetapi juga perubahan pola pikir generasinya yang secara khusus dibahas dalam tulisan ini adalah generasi milenial. Untuk itu gereja perlu mengenali generasi milenial yang juga merupakan dirinya sendiri melalui teori generasi oleh Strauss and Howe. Setelah mengenal generasi milenialnya maka gereja perlu membangun relasi yang bersesuaian dengan karakter milenial. Untuk itu konsep fisika kuantum yang disarankan oleh Keith Anderson akan dipetakan untuk memahami kembali inkarnasi Yesus Kristus sebagai contoh pola relasi yang dapat dikembangkan gereja bagi generasi milenialnya, khususnya pada masa pandemi Covid-19.